PERFORMANCE ANALYSIS OF THE OPENDAYLIGHT SDN CONTROLLER ON TREE TOPOLOGY: THROUGHPUT, JITTER, AND PACKET LOSS - Asruddin Asruddin; Ade Davy Wiranata (Universitas Majalengka, 2025)
Software Defined Networking (SDN) is a modern paradigm in computer network architecture that decouples the control plane from the data plane through centralized network management . This study employs Mininet as a network emulator and OpenDayLight as the controller , with the goal of evaluating Quality of Service (QoS) in an SDN environment using a tree (3,2) topology. The Mininet setup consists of 8 hosts, where the links are configured with a bandwidth of 10 Mbps and a delay of 2 ms. Earlier research only examined basic matrices and did not include further detailed analysis of TCP throughput, UDP throughput, jitter, packet loss, and bandwidth using mathematical methods. The average results obtained in this study are 8.79 Mbit/s for UDP throughput, 8.42 Mbit/s for TCP throughput, 4.12 ms for jitter, and 0.086% for packet loss. The main contribution of this work is: (1) establishing a standard matrix on the receiver side.